Linhas da paisagem pela cidade de Belo Horizonte: dicotomias, forças predatórias e resistência - Júlia Fonseca de Castro; Iuri Francisco Mustafa Cordeiro (e-cadernos ces)
This is an essay that depicts the line of a mountain ridge as an element to contemplate the abyssal condition expressed in the landscape of Belo Horizonte, the capital of Brazil’s Minas Gerais province. The landscape is understood as the mediation of abyssal lines that determine the center and the periphery, based on the dichotomies culture/nature, belonging/non-belonging. This reflection, underpinned by the interpretation of photographic images, discusses the predatory forces of mining activities, real estate speculation in the landscape, resistance movements linked to socio-environmental struggle and the urban landscape production, examining them from culturally diverse references. Lastly, an analysis is done of the line created by the mountain and portrayed in nature paintings on city walls in order to enhance the perception of its symbology.